LEGAL CERTAINTY IN PROVIDING LABOR PROTECTION GUARANTEES FOR HOME WORKERS IN INDONESIAN LABOR LAW - Jan Parlindungan; Budiman, Anwar; Saefullah, Saefullah (JILPR Journal Indonesia Law and Policy Review, 2024)
In Indonesia and in developed and even developing countries, labor is divided into two, namely, formal labor and informal labor. Homeworkers are considered not to be employed by “employers” directly because they are sub-contracted or in other words informal workers, they are not given the protection provided by law to other workers (workers in the formal sector). The purpose of this study is to determine and analyze the legal uncertainty in providing labor protection guarantees for home workers in Indonesian labor law and to understand and analyze a form of legal certainty in providing home worker protection guarantees in Indonesian labor law. This research method is a normative legal research with a normative juridical approach and analyzed qualitatively. The results of this study provide the conclusion that the current Manpower Law does not specifically and specifically address homeworkers causing legal uncertainty of protection guarantees for homeworkers and efforts that can be made to provide legal certainty for the protection of homeworkers are to ensure that homeworkers carry out their work based on work agreements, and the Government through the Ministry of Manpower must immediately make and pass laws that clearly and explicitly regulate the labor rights of homeworkers.